The Influence of the Packing Factor on the Fuel Temperature Hot Spots in a Particle-Bed GCFR - G. Lomonaco; W. Grassi; N. Cerullo (Science and Technology of Nuclear Installations)
In the recent past the so-called GCFR has been again a subject of study by the international scientific community. This type of reactors, although still in a preliminary stage of development, is a very interesting perspective because combines the positive characteristics common to all the fast reactors with those of the reactors cooled by helium. Up to now, almost all the analyses on the GCFR thermodynamic aspects have been performed starting from a “global” point of view: generally the core has been modelled as a porous medium and only the global parameters have been taken into account. The local effects have been included in adhoc corrective peak factors. The analyses carried out in the present research will be devoted to the characterization of the local effects, on a microscopic scale. In order to have reliable “global” nuclear and thermal-fluid-dynamic data, the performed analyses will be based on simulations previously performed using the RELAP5-3D code, assuming as input parameters the ETDR core ones. For each considered case, the variation ranges of the evaluated parameters have been estimated on the basis of the “best” and the “worst” cases. To summarize the obtained results, even in transient conditions, the variations of the considered input parameters are less significant for the local output values if compared to those due to the assumed packing factor. As a consequence, in a more general core calculation, the obtained local temperature (and velocity) values will have to be corrected by a proper factor that would have to take into account the results of this research.